PERAN MAQASHID SYARIAH DALAM MENDUKUNG KEBERLANJUTAN LINGKUNGAN MELALUI IMPLEMENTASI GREEN ECONOMY: STUDI KASUS TENUN IKAT DI PARENGAN - Farikhatus Sa’bandiyah, Umu; Munir Hamid, Ahmad; Ayu, Intan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research aims to analyze the integration of Maqashid syariah principles in supporting environmental sustainability through the implementation of the Green Economy concept, with a case study on the Ikat Weaving industry in Parengan. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study show that the principles of Maqashid Sharia, such as Hifz al-Din, Hifz al-Nafs, Hifz al-'Aql, Hifz al-Mal, and Hifz al-Nasl, have begun to be internalized by weaving industry players, especially in the form of environmental awareness, waste management, and the use of environmentally friendly materials. In addition, Islamic values such as 'adl (justice), ihsan (kindness), and khalifah (human responsibility towards the earth) are in line with the principles of the Green Economy which emphasizes resource efficiency and ecological justice. However, the application of these values still faces challenges, including the limitation of natural raw materials, high production costs, and low market interest in environmentally friendly weaving products. Therefore, synergy is needed between the government, business actors, and the community to support the transition to a sustainable industry based on Islamic values.